2021
DOI: 10.3389/fimmu.2021.611256
|View full text |Cite
|
Sign up to set email alerts
|

The IL23-IL17 Immune Axis in the Treatment of Ulcerative Colitis: Successes, Defeats, and Ongoing Challenges

Abstract: Ulcerative colitis (UC) is a chronic relapsing disorder of the colonic tract, characterized by a dysregulated innate and adaptive immune response to gut microbiota that contributes to the perpetuation of intestinal inflammatory processes. The Interleukin (IL) 23/IL17 axis has been reported to play a key role in UC pathogenesis promoting Th17 cells and cytokines-related immune response. Recently, the blockade of IL23/IL17 pathways has been raised enormous interest in the treatment o several chronic inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 120 publications
0
35
0
5
Order By: Relevance
“…Treatment with ustekinumab was successful for controlling her recurrent CD lesions and led to the subsequent discontinuation of anakinra. This may be due to the fact that ustekinumab, a monocloncal antibody against IL-12p40, which blocks signaling pathways of IL-12 and IL-23, can successfully block IL-1β-mediated Th17 cell activation as well as TNF-α-induced Th1 activation [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with ustekinumab was successful for controlling her recurrent CD lesions and led to the subsequent discontinuation of anakinra. This may be due to the fact that ustekinumab, a monocloncal antibody against IL-12p40, which blocks signaling pathways of IL-12 and IL-23, can successfully block IL-1β-mediated Th17 cell activation as well as TNF-α-induced Th1 activation [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most of the signaling pathways are also involved in immune and inflammatory responses, which are closely related to UC. For example, IL-17, which is secreted by T17 cells, acts as a key mediator in the pathogenesis of intestinal inflammation [ 36 ]. Furthermore, IL-17 can be promoted by IL-23 to increase, thus forming the IL-23/17 axis to amplify the inflammatory response [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both IL-12 and IL-23 are pro-inflammatory cytokines in the interleukin-6 [IL-6] family, which are produced by dendritic cells, monocytes, and macrophages in the intestinal mucosa. 6 , 7 IL-12 is involved in the pathogenesis of several autoimmune processes [including IBD] through its effects on both innate and adaptive immunity. Innate immunity is targeted through the activation of natural killer [NK] cells, NK T cells, and group 1 innate lymphoid cells (ILC1s, which in turn produce TNF and interferon γ [IFNγ]).…”
Section: The Il-12 and Il-23 Pathways And Their Role In Inflammatory ...mentioning
confidence: 99%
“…Indeed, the IL-23 receptor [IL23-R] is expressed on T cells, ILCs, intraepithelial lymphocytes, NK cells, intestinal epithelial cells, and granulocytes, highlighting IL-23’s expansive role in the pro-inflammatory response. 7 Most notable is its involvement in the T helper 17 [Th17] cell activation pathway in combination with transforming growth factor β [TGF-β] and cytokines IL-6, IL-1β, and IL-21, in turn increasing production of IL-17 and thus TNFα, IFNγ, granulocyte-macrophage colony-stimulating factor [GM-CSF], and other inflammatory chemokines through stimulation of endothelial cells and monocytes, as well as IL-21 and IL-22 [ Figure 1 ]. 5–10 Several studies have demonstrated that patients with IBD have increased intestinal, serum, and plasma levels of IL-23 and Th17 cytokines.…”
Section: The Il-12 and Il-23 Pathways And Their Role In Inflammatory ...mentioning
confidence: 99%
See 1 more Smart Citation